Perlawanan Masyarakat Desa Gombong Tasikmalaya Terhadap Gerakan DI/TII - Tisha Maulida Fazriah; Hery Supiarza; Harry Tjahjodiningrat (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
DI/TII is a movement that wants to establish an Islamic State of Indonesia. Led by S.M Kartosuwirjo. The process of spreading gradually for dozens of years in West Java. S.M Kartosuwirjo is a close relative of Ir. Soekarno and still in the same university with HOS Tjokroaminoto. NII was established around August 7, 1949, in the Cisayong area, Tasikmalaya. Coinciding with the second Dutch military aggression. At that time, there was disappointment on the part of Kartosuwirjo because Islam was not the basis of the state. The purpose of this study is to see the resistance of the Tasikmalaya people to DI/TII power. Qualitative methods with a historical approach were used to collect all data. The findings of this study succeeded in obtaining data on organizations that participated in the fight against DI/TII, namely: Village Security Organizations (OKD), Mandatory Training Organizations (WALA), People's Defense Organizations (OPR) and Village Pagers (PD). In addition, this research was also able to obtain information about the story of the resistance against DI/TII from sources who are still alive today. The implications of this research can be a historical reference for the struggle of the Indonesian people for today's young generation.